Analysis of freeze–thaw damage of cement mortars doped with polyethylene glycol-based form stable phase change materials - Sarcinella, Antonella (2024)
The development of construction materials with the integration of phase change materials (PCMs) has been a topic of wide interest in the scientific community, especially in recent years, due to its positive impact on temperature regulation inside buildings. However, little is known about the behavior of materials doped with PCMs when exposed to accidental or severe environments. Currently, a large area of the planet experiences seasonal freeze–thaw effects, which impact the durability and performance of construction materials. Accordingly, the main objective of this study was to evaluate the damage caused by cyclic freeze–thaw actions on the behavior of a cement mortar, including a PEG-based form-stable PCM. An experimental methodology was developed based on the physical and mechanical characterization of mortars under normal operating conditions and after being subjected to freeze–thaw cycles. The results indicated that, under normal exposure conditions, the incorporation of aggregate functionalized with PCM led to a decrease in the mortar’s water absorption capacity, compressive strength, and adhesion. However, its applicability has not been compromised. Exposure to freeze–thaw cycles caused a loss of mass in the specimens and a decrease in the compressive strength and adhesion capability of the mortar.